Influence of some substances on bacterial translocation in the rat - Çetinkaya, Z; Ülger, H; Akkus, MA; Dogru, O; Çifter, Ç; Doymaz, MZ; Özercan, IH (Wiley, 2002)
An experimental study was planned to determine the effect of zinc, levamisole, misoprostol (prostaglandin, analog), and melatonin on the bacterial translocation (BT) that develops in rats after major resection of the liver. To this aim, six groups were formed, each consisting of six rats. Except for the control and sham groups, zinc solution I ml/day, (prepared in a way to include zinc sulfate equivalent of 5 mg pure zinc/ml) was given to the zinc groups, levamisole 25 mg/kg/day to the levamisole group, misoprostol 200 mg/lig/day to the misoprostol group, and melatonin 20 mg/kg/day to the melatonin group for 3 days before the operation. After the preoperative administration of 10(10) colony-forming units of Escherichia coli to the experimental groups, the abdomen was opened in the sham group, and only the connections around the liver were cut. In the test groups a 70% liver resection was undertaken. Laparotomy was carried out on all the rats 24 hours after the operation; blood samples were obtained for polymerase chain reaction (PCR) analysis and tissue samples from the terminal ileum for histopathologic examination. PCR results for BT were positive for the control and sham groups, with the difference between these two groups not significant (p > 0.05). A statistically significant decrease was found in the BT of all the treatment groups compared to the control group (p < 0.05). The histopathologic examination of terminal ileum in the control group revealed that the inflammatory infiltration was significantly less than that in the other groups (p < 0.05).
Keywords: Major Liver Resection; Hepatectomy; Zinc; Overgrowth; Microflora; Cirrhosis; Mortality; Injury